2019
DOI: 10.1002/ca.23412
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography and magnetic resonance imaging study of the variations of the sciatic nerve branches of the pediatric knee: Implications for peripheral nerve blockade

Abstract: In pediatric patients, peripheral anesthetic blockade of the sciatic nerve is useful for postoperative pain relief after orthopedic procedures of the lower limb. The identification of the sciatic and its branches relative to the surrounding anatomical structures of the knee significantly contribute to the successful nerve blockade. However, reports have demonstrated complications arising from the inadequate and inconsistent understanding of the anatomy of the nerves in the knee region. In addition, the paucity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The sciatic nerve has a large number of variations and understanding these is important in the diagnosis and treatment of pathologies involving this nerve [13][14][15]. To our knowledge, the variant described here has not been previously reported.…”
Section: Discussionmentioning
confidence: 75%
“…The sciatic nerve has a large number of variations and understanding these is important in the diagnosis and treatment of pathologies involving this nerve [13][14][15]. To our knowledge, the variant described here has not been previously reported.…”
Section: Discussionmentioning
confidence: 75%
“…This was an expected finding, as it correlates well with our previous study on the pediatric knee region, which demonstrated age-related morphometric changes of the femoral bicondylar width and of the sciatic nerve and its branches relative to their surrounding anatomical structures in the popliteal region. 14 When comparing sexes of each age groups, strong evidence for clinically significant differences was found (Table 1). The SN distances to sacrum (SN-S) and the most medial point of the greater trochanter at the level of coccyx (SN-F2) were longer in females, in 12-16 years and 6-11 years age groups, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The exclusion criteria included MRI scans with poor resolution (e.g., from movement, variation in posture, and fat‐suppressed scans), presence of pathology (e.g., soft tissue tumor), and/or the absence of the axial image plane. Following the exclusion criteria, a total of 84 scans (42 male and 42 female; 28 right side and 56 left side) were used in this study and the sample was grouped into three age categories (0–5, 6–11 and 12–16 years), as in the previous retrospective imaging study that determined the location of the sciatic nerve within the popliteal fossa 14 . For the 0–5 years age group ( n = 17), the mean age was 3.7 ± 1.5 years (range 0.7–5.8), for the 6–11 years age group ( n = 34), the mean age was 8.5 ± 1.4 years (range 6.2–11.0), and for the 12–16 years age group ( n = 33), the mean age was 13.7 ± 1.6 years (range 11.1–15.8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in www.acbjournal.org relative positioning between these neurovascular structures could be due to sexual dimorphism. The positioning of nerves in the popliteal fossa have been found to show significant differences between male and female after puberty due to the formation of muscle mass [10]. Along with the relative positioning differences displayed between male and female, the superficial structures; the SSV, LCSN and MCSN display a high level of variation.…”
Section: Discussionmentioning
confidence: 99%